Infecciones serias en pacientes lúpicos hospitalizados - Noriega Zapata, Erika Janeth (2022)
Introduction. Infections are an important cause of hospitalization in patients with systemic lupus erythematosus (SLE), it produce increased morbidity and mortality. Objectives. To determine the prevalence of serious infections and to know the most frequent etiology in a public hospital of national reference. Methods. Retrospective, descriptive, cross-sectional study in Rheumatology Service of the Guillermo Almenara Irigoyen National Hospital, Lima, Peru. Medical records and records of laboratory tests were reviewed. The registry of hospitalized SLE patients from 2017 to 2019 was analyzed. Those who presented serious infections (received parenteral treatment or died from the infection) were selected. Demographic data (gender and age), time of illness, activity and damage, the number of infectious events, place of acquired infection, place of admission, the etiological agent and the classification of the infectious event were analyzed. Results. 61 (15.6%) of 390 hospitalized lupus patients presented 75 infectious events. They were mainly women (95.1%), young people (15-34 years) (42.6%) with time of disease ≤ 01 year (31.1%). Most infectious events were in-hospital (80%), without empirical treatment (53.3%). Mainly the admission was by transfer of other services (52%). The etiological agent was determined in 53 (70.6%) infectious events. Bacterial (52%) and genitourinary (37.3%) infections were the most frequent. Extended spectrum E. coli beta-lactamase (ESBL) was the most frequently isolated microorganism (28%). Conclusions. The prevalence of serious infections was 15.6%. E. coli ESBL was the most frequently isolated etiological agent, being considered a public health problem.